Relationship between near ground surface temperature and land cover types of eastern lake Khuvsgul (Mongolian Journal of Geography and Geoecology, 2024)
Mongolia, a country located in Central Asia, is known for its extreme climate and distinct natural landscape. However, in recent years, the effects of global warming have accelerated permafrost degradation, leading to significant ecological and environmental disturbances. This study was conducted to investigate these changes and contribute to the preservation of Mongolia's pristine nature and unique environmental structure. Specifically, the research focuses on the relationship between thawing permafrost and temperature on the eastern shore of Lake Khuvsgul, considering natural factors such as vegetation and snow cover. In the study area, 31 surface temperature monitoring devices were installed at 300-meter intervals across four distinct types of ground cover: grassland, wetland, forest, and shrubland. These temperature readings were then used to calculate various indices. The highest ground surface temperature during the summer, 28.2°C, was recorded at point A-14, while the lowest winter temperature, -19.31°C, was observed at point A-17, both located in grassland areas. The frost number, an index used to measure thawing, registered values below 0.5 only at grassland points, indicating a higher likelihood of permafrost presence at other locations. Additionally, the N-factor, which reflects seasonal temperature variations, was found to be lower in forested areas and higher in grassland areas. Points located in forests were notably cooler in the summer and warmer in the winter compared to those points in grasslands. The surface temperature during winter was also affected by the snow accumulation that year, becoming colder as the snow cover increased. Furthermore, the N-factor decreased with thicker snow during the winter season. Snow cover duration in 2022-2023 was 9-11 days longer compared to the previous year (2021-2022).Монгол орны нуурын геоморфологийн шинэ мужлалМонгол орон нь төв Азид орших эрс тэс уур амьсгалтай орнуудын нэг бөгөөд байгалийн зүй тогтоц, бүтцээрээ бусад орнуудаас онцлогтой. Сүүлийн жилүүдэд явагдаж буй дэлхийн дулааралтай холбоотойгоор Монгол орны цэвдгийн алдрал эрчимжиж байгаль, экологийн тэнцвэрт байдал алдагдсаар байна. Тийм ч учраас тухайн бүс нутгийн байгалийн унаган төрх, өвөрмөц бүтцийг хадгалах зорилгоор энэхүү судалгааг хийх шаардлага тулгараад байна. Бид тус судалгааны хүрээнд Хөвсгөл нуурын зүүн эрэгт орших цэвдэг болон температур хоорондын хамаарлыг байгалийн хүчин зүйлс болох ургамал, цасан бүрхэвчтэй холбон тайлбарлахыг зорьсон. Судалгааны талбайд нийтдээ 31 ширхэг гадаргын температур хэмжигч багажуудыг 300 метрийн зайтайгаар өөр өөр дөрвөн газрын бүрхэвчийн хэв шинж бүхий байршилд (Нуга, Намаг, Ой, Сөөг) суурилуулан тэдгээрийн утгуудыг ашиглаж зарим индексүүдийг тооцоолсон. Хөлдөлт болон гэсэлтийн индексийн хувьд газрын гадарга дээрх хамгийн дулаан температур зуны улиралд А -14 цэгт 2282°C байсан бол хамгийн хүйтэн температур өвлийн улиралд А-17 цэгт -1931°C-тэй тус тус нугад байрлах дэх цэгүүдэд бүртгэгдсэн байна. Frost number буюу цэвдгийн индекс нь зөвхөн нугад орших цэгүүдэд 0.5-аас доош утгуудыг үзүүлж бусад цэгүүдэд цэвдэг байх магадлал өндөртэйг илтгэсэн. Харин хүйтэн болон дулааны улирлын N-factor нь ойтой цэгүүдэд бага, нугад байх цэгүүдэд өндөр байгаа нь ажиллагдсан. Зуны улиралд ойтой цэгүүд, нугад орших цэгүүдээс харьцангуй сэрүүн байдаг бол өвлийн улиралд дулаан байдаг нь ажиллагдсан. Мөн өвлийн улирлын гадаргын температур тухайн жилд орсон цасны жингээс хамааран сэрүүсэж байсан бол цасны зузаанаас хамаарч өвлийн улирлын N-factor багасаж байгаа зүй тогтол гарсан. 2022-2023 оны тогтвортой цасан бүрхүүлтэй өдрүүд өмнөх оныхоос (2021-2022) 9-11 хоногоор урт үргэлжилсэн байна. Түлхүүр үгс: Цэвдэг, Температур, Нуга, Ой, Хөвсгөл нуур